2022
DOI: 10.1002/cbl.30623
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID‐19 pandemic on pediatric chronic illness groups

Abstract: The COVID‐19 pandemic has had profound impacts on children and families, with widescale disruptions in many aspects of individual, family, school, and peer functioning. For children and adolescents, the pandemic has contributed to increased prevalence of depression, anxiety, eating disorders, and suicidality, particularly among adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…The study also highlights the vulnerability of children and adolescents with preexisting severe illnesses to the deterioration of their health conditions, especially in terms of mental health. These findings are consistent with a recent German population-based survey study [31][32][33][34][35]. Di Renzo et al, reported a population-based survey of daily lifestyle and dietary behaviors in Italy as early as April 2020, at the height of the first COVID-19 lockdown.…”
Section: Discussionsupporting
confidence: 89%
“…The study also highlights the vulnerability of children and adolescents with preexisting severe illnesses to the deterioration of their health conditions, especially in terms of mental health. These findings are consistent with a recent German population-based survey study [31][32][33][34][35]. Di Renzo et al, reported a population-based survey of daily lifestyle and dietary behaviors in Italy as early as April 2020, at the height of the first COVID-19 lockdown.…”
Section: Discussionsupporting
confidence: 89%